2021
DOI: 10.1371/journal.pone.0251231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the gut bacterial microbiome and metabolome of girls and women with Rett Syndrome

Abstract: Background Gastrointestinal problems affect the health and quality of life of individuals with Rett syndrome (RTT) and pose a medical hardship for their caregivers. We hypothesized that the variability in the RTT phenotype contributes to the dysbiosis of the gut microbiome and metabolome in RTT, predisposing these individuals to gastrointestinal dysfunction. Objectives We characterized the gut bacterial microbiome and metabolome in girls and young women with RTT (n = 44) and unaffected controls (n = 21), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 66 publications
(94 reference statements)
5
24
0
Order By: Relevance
“…Transmission of endogenous glutamate concentrations was proven to play a role in characterizing the durations of sleep and wakefulness [ 63 ]. In human research, fecal glutamate has been shown to be significantly lower in RTT females than unaffected controls [ 64 ]. although the specific mechanisms of REM sleep remain unclear [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of endogenous glutamate concentrations was proven to play a role in characterizing the durations of sleep and wakefulness [ 63 ]. In human research, fecal glutamate has been shown to be significantly lower in RTT females than unaffected controls [ 64 ]. although the specific mechanisms of REM sleep remain unclear [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is metabolized by the gut microbiome [ 106 ]. In RTT, the gut microbiome, depending on clinical severity score, has been reported to shift towards a less diverse and pro-inflammatory composition [ 38 , 107 ]. This may result in an altered bioavailability of non-metabolized rutin in Mecp2 −/y mice.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic studies in RTT are currently in their early stages but bear the potential to provide global insights into pathogenic mechanisms. Recently, the suitability of this approach was demonstrated in a first metabolomics study on RTT patient-derived blood samples [ 37 ], and the characterization of the gut microbiome and metabolome in RTT patients [ 38 ]. An earlier pilot metabolic screening in male Mecp2 -null ( Mecp2 −/y ) mice analyzed full brain extracts by means of high-resolution magnetic resonance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small number of published articles, we decided not to exclude the studies which involved both children and young adults. Adult patients were included in one AN study, two ADHD studies, MDD and Rett syndrome study [16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study published to date involved children and adolescents with RTT along with young women [20]. Alpha diversity as well as beta diversity between patients and healthy controls did not differ signi cantly.…”
Section: Gut Bacteria Pro Les In Children With Autism Spectrum Disordermentioning
confidence: 92%